Bibliometric Analysis Relational Capital On Business - Fitnantyo Bimawan; Kundori Kundori; Andar Sri Sumantri (CV. Ulil Albab Corp, 2024)
The aim of the research is to identify themes and research trends by assessing them based on keywords. To understand scientific understanding and trends in the research field by identifying articles and references that are highly cited. To obtain bibliomatric results using mapping and visualization software. To identify the main research topics and themes that often appear in research on Relational Capital in business. The data source was taken from the Google Scholar database. Data collection method using the publish or perish application. Then the data was selected according to the research topic and completed using Mendeley Desktop. Data is processed using VOSViewer. Search results based on authors using VOSViewer found 688 authors with a minimum number of authors of 3 found at 19 meetings. Furthermore, 54 keywords were found and divided into 11 different clusters. The keywords relational capital and intellectual capital are the most research topics. Conclusion Relational capital is an important component of intellectual capital which refers to the value generated from an organization's relationships with external stakeholders, such as customers, suppliers, partners and society.